Induced Abortion and Spontaneous Early Pregnancy Loss Focus on Management - Lakhno, Igor (IntechOpen, 2020)
This book is focused on the protection of female reproductive health. Artificial pregnancy termination is known to be associated with an increased risk of infertility, spontaneous pregnancy loss, and other gestational pathologies. Since family planning is a system for the prevention of unwanted pregnancy, the current situation of the spread of induced abortion in different parts of the world is analyzed. Early pregnancy loss is a wide-ranging problem in medicine and habitual abortion is a real tragedy for women in their childbearing years. The different pathogenetic scenarios of spontaneous pregnancy termination are described and the possible interventions for prevention contributing to beneficial outcomes are discussed.